Prediction Model of Pre, Peri-, and Postnatal Factors for Early Childhood Caries in Stunted Children of Juwiring, Central Java, Indonesia - Badruddin, Iwany Amaliah; Rahardjo, Anton; Ramadhani, Atik; Darwita, Risqa Rina; Putri, Lintang Andarini (Indonesian Dental Association, 2025)
Introduction: The life course approach highlights how early life, beginning with fetal growth, influences future disease risk. Oral health studies in Indonesia using this approach are still limited. This study examined the relationship between ECC status and retrospective data on stunted children under three and their mothers’ pregnancy history at Juwiring District Community Health Center. Objective: This study aims to examine the influence of pre, peri-, and postnatal factors on ECC occurrence in stunted children in Juwiring Regency, Central Java. Methods: Secondary data of pre, peri-, and postnatal information from 265 stunted children were obtained from the medical records. Oral examination was assisted by local dentists from the health center. Multiple logistic regression analysis was performed to construct a prediction model and determine the factors with the greatest influence on dental caries in stunted children in Juwiring District. Results: The prevalence of dental caries was 69.1% in 246 subjects. The variables in the final prediction model for factors related to ECC were the mother's perception of her child's dental problems, the mother's education level, the mother’s knowledge of dental caries, and the child’s stunting status. The most influential factor was the mother's perception of her child's dental problem, with the highest odds ratio (OR) of 5.1 (1.83–14.23). Conclusion: This study revealed that prenatal factors related mothers’ education level and postnatal factors related to mothers’ perceived dental problems, poor knowledge of dental caries and children’s stunting status were included in the ECC prediction model for the stunted children of Juwiring District.